Investment climate and regional development in the Philippines - Ernesto M. Pernia; John Michael Ian Sioson Salas (University of the Philippines, School of Economics (UPSE), 2005)
This paper examines the Philippines' investment climate in its many dimensions, relating these to the performance of the economy at the national, regional, and provincial levels. The central thesis is that the economy's slow growth over the past two decades or more can be attributed in large measure to its poor investment climate that constricted capital formation and hampered the productivity improvements and competitiveness of firms; by extension, the differential development of regional and provincial economies can be explained by, among other factors, differences in their investment climates. From a cross-country comparative perspective, the Philippines appears to rate quite poorly in terms of a number of investment climate dimensions, including entry and exit of firms, regulatory burden and corruption, and infrastructure. These macro-level observations are largely corroborated by the results of more rigorous analysis of micro (firm-level) and provincial and regional data. The paper concludes that addressing the deficiencies of the investment climate, complemented by other relevant policy reforms, at the national and local levels, would significantly contribute to enhancing the economy's productivity and long-run growth, as well as raise the performance of the lagging regions towards the level of the leading regions.
Keywords: 330